Physician Burnout Through the Female Lens: A Silent Crisis - Yeluru, Hemasree; Newton, Heather L.; Kapoor, Rupa (Frontiers in Public Health, 2022)
Physician burnout, the emotional exhaustion and depersonalization that arises from job fatigue and dissatisfaction, is a rapidly growing problem. Although burnout has been a recognized problem for decades, our healthcare system has yet to devise a sustainable solution. Additionally, burnout does not affect all physicians in the same way- women physicians have disproportionately higher rates of burnout than male physicians. Burnout poses a tremendous risk to our public's health with its severe and debilitating effects on both physician and patient health alike. We must intervene as early as medical school and residency at both the systemic and individual levels to combat burnout. Clinical leadership training might be one sustainable approach to begin addressing burnout in female physicians.